Integration of Machining Inspection Sensors and Software - Sawula, Alan D. (My University, 2013)
Ideally, the nominal design of a part or assembly, created with 3D Computer-Aided Design and Manufacturing (CAD/CAM) software, can be consistently fixtured and machined. In reality, process conditions vary, and feedback and correction methods such as integrated on-machine inspection, analysis, and process adjustment, are required.
On-machine inspection based on touch trigger probes is well established, but limited motion control computing capability restricts analysis to simple arithmetic. This prevents on-line use of known whole part mathematical analysis software that implements the part salvaging intentions of modern Geometric Dimensioning and Tolerancing (GD&T) standards. Additionally, no CNC integrated method exists for geometrically adjusting nominal tool paths so that an in-tolerance final part is produced. Machine tool support for high data rate sensors such as laser scanners is also lacking.
This thesis reports progress towards bidirectional integration of machine tool mounted inspection sensors with GD&T analysis software, and subsequent toolpath adjustment. The concepts are demonstrated using a fixture consisting of three datum spheres and a workpiece. The fixture is clamped in the CNC machine, datum spheres are measured, and after mathematical data fitting and registration, an in-tolerance final part is produced. To facilitate multiple tests, a tool path is split into four and machined in four poses with measurement and tool path adjustment for each pose. Preliminary integration of a laser scanner with axis scales and computer software was also accomplished.
Keywords: CNC; CMM; GD&T; Inspection Sensors; Computer-Aided Engineering and Design; Manufacturing; Computer-Aided Engineering and Design